Analysis of Students’ Mathematics Conceptual Understanding Based on Differences in Mathematics Thinking Styles - Fauziyah, Nur; Hakim, Lukman El (Jurnal Pendidikan MIPA, 2025)
This study aims to examine students’ thinking processes in understanding concepts by considering the variations in mathematical thinking styles. This research is motivated by the finding that students demonstrate different thinking styles and intelligence, which is evident in the distinct ways they represent and design their learning approaches. This study employs a qualitative research method, using interviews based on tasks through the think-aloud method for data collection. The research instrument consists of a written test designed to probe students' thinking processes in understanding mathematical concepts according to the indicators of conceptual understanding used in this study. The researchers used time triangulation techniques to ensure the validity of the research data. The data analysis followed a structured process: data classification, reduction, presentation, interpretation, and conclusion drawing. The research subjects comprised three students with different mathematical thinking styles, namely visual, analytical, and integrated, who shared similarly high mathematical ability levels. The findings show that subjects with a visual mathematical thinking style create representations in the form of images, tables, or graphs for each indicator of understanding. Subjects with an analytical mathematical thinking style create representations in the form of verbal sentences or mathematical models that are rich in mathematical symbols and variables. While subjects with an integrated mathematical thinking style create representations in the form of verbal sentences, images, diagrams, mathematical symbols, tables, mathematical models, or graphs. The study concludes that while the type of mathematical thinking style—visual, analytical, or integrated—does not significantly influence the depth of students’ conceptual understanding, it does shape the strategies they employ to construct that understanding. All three students demonstrated the ability to interpret, exemplify, classify, summarize, infer, compare, and explain concepts effectively, a consistency attributed to their shared high level of mathematical proficiency.     Keywords: mathematics, conceptual understanding, mathematical thinking style, cognitive process.